Hepatic epithelioid hemangioendothelioma: An international multicenter study. Issue 9 (September 2020) - Sanduzzi-Zamparelli, Marco; Rimola, Jordi; Montironi, Carla; Nunes, Vinicius; Alves, Venancio Avancini Ferreira; Sapena, Víctor; da Fonseca, Leonardo Gomes; Forner, Alejandro; Carrilho, Flair José; Díaz, Alba; Fuster, Carla; Ferrer, Joana; et al.
Abstract: Background and aims: Hepatic epithelioid hemangioendothelioma is an ultra-rare hepatic vascular tumor, diagnosed more frequently in females. The knowledge about this tumor derives mainly from small case series with sub-optimal treatment outcomes. The aim of this study is to identify the clinical and radiological issues helpful to develop an international prospective registry. Methods: We conducted an international multicentric and retrospective study of patients with hepatic hemangioendothelioma. The clinical, pathological and radiological images collected during follow-up were reviewed. Central radiological revision was performed and 3 patterns of contrast were defined. Results: Between 1994 and 2016, 27 patients with hepatic hemangioendothelioma were identified in three institutions but the final diagnosis was hepatic angiosarcoma in one. The majority were females, median age was 38.7-years and 17 patients were asymptomatic at diagnosis. No patient had Two out of ten (20%) patients had surgical specimens with positive macro-vascular invasion and 50% had extrahepatic disease, and the most frequent pattern was the progressive-central-contrast-uptake. After a median follow-up of 6.7-years, the 5- and 10-year survival rates are 91.5% and 51.9%, respectively. Conclusions: This multicentric study shows the heterogeneous profile of patients with hepatic hemangioendothelioma, reflecting the need to establish a reference network in order to better characterize these patients and ultimately develop a personalized treatment strategy.